Analisis Potensi Wisata Ha Long Bay Terhadap Perekonomian Vietnam - Hardi Alunaza; Bastian Andhony Toy (Indonesian Journal of Tourism and Leisure, 2020)
This paper aims to explain how Ha Long Bay's tourism potential is one of UNESCO's world heritage and its implications for economic development in Vietnam. The author uses the national branding concept to analyzing the related phenomena. The results show that Ha Long Bay tourism increased the Vietnam's economic development due to an increase in economic growth through tourism sector revenues in GDP (Gross Domestic Product) of 9.3 percent. This sector is also able to provide employment to 3.7 percent of the total workers in Vietnam. Vietnam has also been named as one of the 10 countries in the world with the fastest growth rate of recovery in the tourism sector after the global monetary crisis in 2008-2009. The existence of a positive assessment from the international community certainly has implications for increasing visits from tourists and makes Ha Long Bay has its own charm and competitiveness in the global tourism industry.